2011
DOI: 10.1108/17554171111155357
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for Islamic home financing: a case study of Pakistan

Abstract: Purpose -The aim of this research is to examine the selection criteria of customers for Islamic home financing in the context of Pakistan and to examine these factors with respect to gender, age, income, and occupation. Design/methodology/approach -This study uses a quantitative approach to investigate the choice criteria for Islamic home financing. All 18 independent variables are taken from previous research; for their analysis, descriptive statistics, independent sample t-tests and ANOVA was used. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 23 publications
6
74
2
1
Order By: Relevance
“…It might attribute to the fact that IBs in Kuwait are well-known among customers in Kuwait. The finding is consistent with the results reached by Hamid and Masood (2011) who found mass media is less influence on attract customers. However, it is not agreement with earlier studies like Ismail et al (2014) in Malaysia.…”
Section: Selection Criteriasupporting
confidence: 83%
See 3 more Smart Citations
“…It might attribute to the fact that IBs in Kuwait are well-known among customers in Kuwait. The finding is consistent with the results reached by Hamid and Masood (2011) who found mass media is less influence on attract customers. However, it is not agreement with earlier studies like Ismail et al (2014) in Malaysia.…”
Section: Selection Criteriasupporting
confidence: 83%
“…It refers to the fact that customers are influenced by responsive attitude of the bank staff. The finding is consistent with the results reached by Hamid and Masood (2011) and Awan and Azhar (2014) and Zulfiqar et al (2014) who provided evidence that quality of service is the influential factor for the customer in IBs. However, the finding is inconsistent with the results reached by previous empirical studies that reported by Abduh and Omar (2012) who provided evidence that quality of service provided by bank staff play minor influence on customers in selecting IBs in Malaysia.…”
Section: Selection Criteriasupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the objective of Islamic bank which is to promote well-being of both the bank and the customer. There are two works which replicated this study notably Abdul- Hamid et al (2011) and Hamid and Masood (2011), however but they are varied in terms of research objectives and geographies. A study by Abdul- Hamid et al (2011) focuses on factors that influence the adoption of Islamic home financing.…”
Section: Studies On Musharakah Mutanaqisah Home Financingmentioning
confidence: 63%